The character of the alienated woman in Falah Shaker’s theatrical texts, "The Savage Wedding as a model" (Al-Academy, 2024)
The research (The Character of the Alienated Woman in Falah Shaker's Theatrical Texts, The Wild Wedding Play as a Model) was concerned with studying (alienation) and its impact on the woman's character and the construction of society as a whole, as the process of sound construction of any society and the consolidation of the family values ​​system depends on the woman's character and her cultural and social presence, and the forms of her presence in the theatrical text, regardless of the human cultures to which she belongs. The research included four chapters. The first chapter included the research problem, which cantered around the following question: (What is alienation and what is its impact on the woman's character in Falah Shaker's theatrical texts, The Wild Wedding Play as a Model?), and the importance of the research, which was attributed to the necessity of studying (alienation) in Falah Shaker's theatrical texts, as it is considered the inauguration of one of the social phenomena that many researchers in the field of theatre have not had the opportunity to delve into before. The need for it stems from the fact that this research will benefit researchers and students in colleges and institutes of fine arts and those working in the field of theatrical literature and determining the goal that focused on identifying the topic (the character of the alienated woman in Falah Shaker's theatrical texts, the play The Wild Wedding as a model), in addition to the procedural definitions of the terms included in the title of the research. As for the second chapter (the theoretical framework), it consisted of two sections, in addition to mentioning the indicators that resulted from the theoretical framework. The researcher dealt in the first section: the character of the alienated woman. As for the second section, the researcher dealt in it: to study alienation in the global theatrical text. The researcher devoted the third chapter to the research procedures, in which the research community was identified, which includes one research sample. At the end of her research, the researcher concluded by mentioning the results that emerged from the analysis of the research sample, including:1- The character of the alienated woman or mother tries to search for her child who was lost in the womb of sin and the shadows of absence. She tries to restore what remains of him, as she suffers from a sense of guilt towards him.2- Alienation is closely associated with the heroine character.3- The alienated character in the play (The Savage Wedding), that is, the character of the woman, tries to escape from the past and aspires to reassurance, tranquillity, and the achievement of dreams, but to no avail, as she was unable to achieve her dreams that she had always dreamed of or her ambitions.The researcher built the conclusions according to the results, then presented a set of recommendations accompanied by some suggestions that she found complementary to the research